Protective effects of nebivolol on ovarian ischemia–reperfusion injury in rat. Issue 11 (22nd September 2020) - Colak, Sabri; Gurlek, Beril; Topcu, Atilla; Tumkaya, Levent; Mercantepe, Tolga; Yilmaz, Adnan
Abstract: Aim: Ovarian torsion is a common gynecological emergency of reproductive ages, occurring at rates of 2.7–7.4%. This study aimed to evaluate the antioxidant effects of Nebivolol (NEB) and histopathological changes in experimental ischemic (I) and ischemic‐reperfusion (I/R) injury in rat ovaries. Methods: Forty‐eight adult female rats were randomly separated into six groups as group 1 (control) receiving an oral saline solution for 3 days; group 2 (I) that underwent ischemia for 3 h with the application of atraumatic vascular clips; group 3 (I/R); group 4 (I + NEB) receiving 10 mg/kg NEB by oral gavage 30 min prior to the ischemia induction; group 5 (I/R + NEB) receiving 10 mg/kg NEB, and group 6 (control + NEB) receiving oral 10 mg/kg NEB for 3 days before ischemia induction followed by consequent reperfusion. Ovarian tissue damage was scored by histopathological analysis. Ovarian tissue malondialdehyde (MDA) and glutathione (GSH) levels were measured biochemically. Results: The levels of MDA and tumor necrosis factor‐alpha (TNF‐α), and TUNEL assay positivity scores increased in the I and I/R groups. GSH levels decreased in all case groups ( P  < 0.05). The oral administration of NEB (10 mg/kg) to the I‐ and I/R‐groups reduced the levels of MDA and TNF‐α and TUNEL assay immunopositivity scores ( P  < 0.05). GSH levels increased in the treatment groups. Conclusion: The current experimental ovarian torsion study suggests a protective role for NEB against I and I/R injury in rat ovaries. NEB may be a novel agent for decreasing ovarian I/R injury.